Respostas

2014-03-04T13:01:11-03:00
1º) sqrt (sqrt (3)*sqrt (5)*sqrt (3))

2º sqrt (3) sqrt(5) sqrt (3) = 3 sqrt (5): sqrt (3 sqrt (5))
Formula ( Para a> = 0, sqrt (ab) )= sqrt(a)*sqrt (b).
sqrt (3 sqrt (5)) = sqrt (sqrt (5)) sqrt (3): sqrt (sqrt (5)) sqrt (3)

3º) Formula ( Para todo a> = 0, sqrt (sqrt (a)) ) = a ^ (1/4).
     Usar passo 3 para sqrt (sqrt (5))

4º) Multiplique expoentes
sqrt (sqrt (5)) = 5 ^ (1/4):

Resposta: 5^(1/4) sqrt (3)

OBS: sqrt = n^1/2

Fiz passo a passo, pra você visualizar melhor vai escrevendo linha por linha.